2022
DOI: 10.1177/10499091211072850
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning for Emergency Department Patients With COVID-19 Infection: An Assessment of a Physician Training Program

Abstract: Objective Coronavirus Disease 2019 (COVID-19) has heightened the importance of advance care planning (ACP), particularly in the emergency department (ED). The objective of this study was to determine the effect of an educational program for emergency physicians on ACP conversations in the ED during the COVID-19 pandemic. Design This was an observational pre-/post-interventional study. Setting This study was conducted at a Southeastern U.S. academic ED. Participants 143 patients with confirmed COVID-19 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…8,9 In randomized trials, ACP has been shown to positively influence patients' care satisfaction and caregiver distress; however, health status (e.g., quality of life and mental health), rates of goal concordant care, and healthcare utilization outcomes have been mixed. [10][11][12][13] In the setting of the COVID-19 pandemic, there have been multiple interventions developed, such as communication guides, [14][15][16] new workflows 17 and COVID-19 goals of care videos, 18 to help providers conduct ACP discussions in the context of COVID-19 infection. [19][20][21][22][23] However, despite the overwhelming consensus on their necessary roles during the COVID-19 pandemic, the rates of ACP for patients admitted for COVID-19 remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In randomized trials, ACP has been shown to positively influence patients' care satisfaction and caregiver distress; however, health status (e.g., quality of life and mental health), rates of goal concordant care, and healthcare utilization outcomes have been mixed. [10][11][12][13] In the setting of the COVID-19 pandemic, there have been multiple interventions developed, such as communication guides, [14][15][16] new workflows 17 and COVID-19 goals of care videos, 18 to help providers conduct ACP discussions in the context of COVID-19 infection. [19][20][21][22][23] However, despite the overwhelming consensus on their necessary roles during the COVID-19 pandemic, the rates of ACP for patients admitted for COVID-19 remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside the telehealth-related innovations that have facilitated ACP conversation, this review also revealed notable innovation and flexibility in ACP documentation accommodating the constraints of the pandemic [ 116 , 117 , 118 , 119 , 120 , 121 , 126 , 127 , 128 , 135 ]. These innovations, which have facilitated the completion and accessibility of ACP documents, include streamlining the ACP processes [ 127 ], modification of the electronic health records to facilitate ACP documentation [ 71 ], the use of user-friendly [ 83 ] and electronic ACP forms [ 116 , 121 , 126 , 145 ], COVID-19-specific ACP documentation [ 135 ], apps to capture electronic signatures [ 63 ], electronic means of signature witnessing [ 138 ], and drive-by document signing [ 63 ]. As an example of how ACP documentation innovations can increase ACP documentation, McFarlane and colleagues describe a 296% increase in usage of the NHS’s Coordinate My Care services ( , accessed on 14 May 2023), which takes an innovative integrative approach to care planning (including an ACP component) [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…Es ist also keine Entscheidung aufgrund medizinischer Indikationen. Eine frühzeitige Planung und Willensäußerung seitens des Patienten [66] und ein klares Verständnis für palliative Situationen im Behandlungsteam sind die Grundvoraussetzungen für eine optimale Behandlung [67].…”
Section: Palliativmedizinische Aspekte Bei Geriatrischen Patientenunclassified